2020
DOI: 10.3390/pathogens9050383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the FIV Status and Chronic Gingivitis on Feline Oral Microbiota

Abstract: Feline chronic gingivostomatitis (FCGS) has an unclear pathogenesis with the oral microbiome and viral infections, such as feline immunodeficiency virus (FIV), thought to contribute. Although the relationship between the FIV status and FCGS is not clear, one theory is FIV-induced immune dysregulation could contribute to oral dysbiosis, promoting FCGS development. To further understand the relationship between FCGS, FIV infection, and the oral microbiome, oral cavities of forty cats fitting within 4 groups (FIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
8
0
3
Order By: Relevance
“…This may suggest an antagonistic relationship between the two taxa. A significant enrichment of Xanthomonadaceae was also previously reported for cats without gingivitis, which aligns with the data presented here [ 23 ]. In vitro studies may be needed to further investigate this.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may suggest an antagonistic relationship between the two taxa. A significant enrichment of Xanthomonadaceae was also previously reported for cats without gingivitis, which aligns with the data presented here [ 23 ]. In vitro studies may be needed to further investigate this.…”
Section: Discussionsupporting
confidence: 93%
“…However, a previously published study in cats suffering from FCGS demonstrated a higher microbial diversity in cats with FCGS [ 18 ], which is contrary to the results obtained here. Another study observed no differences in the diversity of the bacterial profile of cats with and without chronic gingivitis [ 23 ]. The mycological analysis, however, showed a significantly lower fungal diversity in healthy cats compared to cats with FCGS ( Figure 1 b,c).…”
Section: Discussionmentioning
confidence: 99%
“…В результате этого активизируется не только условно патогенная микрофлора, но даже и у сапрофитной микробиоты могут возникать факторы патогенности. Такая ситуация создает широкие возможности для формирования различных сочетаний микрофлоры в биотопах организма, приводящих к возникновению сложнокомпонентных и, зачастую, недоброкачественных микробиоценозов [7][8][9].…”
Section: терапия животныхunclassified
“…One female presented mammary adecarcinoma and neutropenia while another cat presented gingivostomatitis. Both of these conditions can be attributed to FIV infection given that the retrovirus predisposes hosts to various infections including those of the oral cavity [40,57], and FIV infection is associated with a greater risk of neoplasm development, including mammary tissue neoplasms [58]. Cytopenias, including neutropenia, are frequent alterations found in FIV-positive cat blood counts [21,[49][50][51].…”
Section: Full Textmentioning
confidence: 99%